2020
DOI: 10.2106/jbjs.19.01471
|View full text |Cite
|
Sign up to set email alerts
|

Goal Attainment Scaling Rehabilitation Improves Satisfaction with Work Activities for Younger Working Patients After Knee Arthroplasty

Abstract: Background: Knee arthroplasty (KA) is increasingly performed in relatively young, active patients. This heterogeneous patient population often has high expectations, including work resumption and performance of knee-demanding leisure-time activities. Goal attainment scaling (GAS) may personalize rehabilitation by using patient-specific, activity-oriented rehabilitation goals. Since unmet expectations are a leading cause of dissatisfaction after KA, personalized rehabilitation may improve patient s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 43 publications
1
30
0
Order By: Relevance
“…Incorporating a client-centered approach by the treating specialists could result in a more tailored treatment program which could enhance satisfactory short- and long terms results. A nice example is the recent study on Goal Attainment Scaling among working age knee arthroplasty patients that shows that preoperatively formulated patient-centered activity goals resulted in an increased satisfaction for these work-related activities until 12 months post-operatively [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating a client-centered approach by the treating specialists could result in a more tailored treatment program which could enhance satisfactory short- and long terms results. A nice example is the recent study on Goal Attainment Scaling among working age knee arthroplasty patients that shows that preoperatively formulated patient-centered activity goals resulted in an increased satisfaction for these work-related activities until 12 months post-operatively [ 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, occupational health professionals around the world face the urgent challenge to develop evidence of how to improve a patient’s ability for sustained employability – as an essential value in life – after surgery ( 19 ). Promising initiatives have recently been described although not validated for work participation yet ( 20 23 ). More importantly, occupational health professionals should play a primary role in reducing the steep increase in replacement surgery by mitigating the risk of knee OA.…”
mentioning
confidence: 99%
“…This was in line with previous observations [ 24 , 25 ], where patient-reported outcomes suggest a correlation between preoperative levels of physical activity and RTS capacity after TKA. Most patients return to low-impact sports after TKA with popular activities such as bicycle riding, swimming, hiking, and sometimes skiing (alpine) [ 26 , 27 , 28 , 29 , 30 ]. Previous similar studies observed that most surgeons are rather reluctant to recommend participation in high-impact sports after TKA [ 31 , 32 ], leading concerns were aseptic loosening due to increased wear and debris [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical outcome measurements may not be able to differentiate between the groups and standard post-operative rehabilitation program may not meet the needs of every patient. As recently demonstrated, goal attainment scaling (GAS) may be one approach to improve satisfaction for active patients with high RTS expectations [ 29 , 83 ].…”
Section: Discussionmentioning
confidence: 99%